Associations of self-reported sleep disturbances, sleep onset, and duration with gallstone disease risk - Bao, Dongjun; Bao, Kunming; Fu, Xiaoxian; Xie, Xueping; Ma, Xin; Huang, Zhidong; Que, Rongcai; Gu, Wenjun; Lu, Shengyou (Frontiers in Nutrition, 2025)
BackgroundThe role of sleep disturbances in gallstone disease risk remains unclear. We aimed to examine the associations between sleep disturbances and gallstone disease risk.MethodsWe analyzed data from 9,059 participants in the NHANES survey (2017–2020). The primary outcome of this study was gallstone disease. Sleep disturbances included trouble sleeping, early or late sleep onset time, and long or short sleep duration. Multivariate logistic regression analysis was employed to evaluate the associations between sleep disturbances and gallstone disease risk.ResultsAfter adjusting for confounding factors, trouble sleeping was associated with an elevated risk of gallstone disease, with the odds ratio (OR) of 1.47 (95% confidence interval [CI]: 1.01–2.15), compared to those without trouble sleeping. In further stratified analysis, among individuals with trouble sleeping, no significant associations were found between different sleep onset intervals, sleep duration and gallstone disease risk. Among participants without trouble sleeping, the sleep onset interval of 23:00 to 00:00 was associated with a significantly increased gallstone disease risk compared to the reference sleep onset interval of 22:00–23:00, with an OR of 1.61 (95% CI: 1.06–2.45). Short sleep duration (<6 h) was associated with a significantly reduced gallstone disease risk compared to the reference sleep duration of 6–8 h, with the OR of 0.43 (95% CI: 0.25–0.75).ConclusionThis study demonstrates that trouble sleeping increases the risk of gallstone formation, independent of sleep onset time and sleep duration. Among those without trouble sleeping, a sleep onset time between 23:00–00:00 is associated with a higher risk, while short sleep duration (< 6 h) appears protective.